PUBLIC POLICY INNOVATIONS IN ECONOMIC GROWTH - Adinata, Uslan; Nadiddin Alhanif, Muhammad (International Conference on Humanity Education and Society (ICHES), 2025)
This study investigates how public policy innovations catalyze national economic growth amid global disruptions and structural transformation. Unlike prior research that primarily emphasizes fiscal or monetary policies, this work positions policy innovation as a core driver of sustainable growth ecosystems. Employing an exploratory qualitative approach through a literature review of 20 peer-reviewed nstudies from 2021–2025, the research evaluates policy impact across strategic sectors, including digital investment, green economy, SMEs, and bureaucratic reform. Findings reveal that policies incorporating digital technology, inclusive governance, and fiscal incentives significantly enhance national productivity and economic resilience. The study contributes to the formulation of an innovation-based policy framework responsive to global economic dynamics and sustainable development challenges.